Cognitive predictors of everyday functioning in women with HIV: findings from the women’s interagency HIV study - David E. Vance; Lang Lang; Pauline M. Maki; Danyang Yu; Raha Dastgheyb; Yuezhe Wang; Gayle Springer; Kathryn Anastos; Deborah R. Gustafson; Kathleen M. Weber; Derek M. Dykxhoorn; Joel Milam; et al. (BMC Neurology)
Abstract Background As the number of older people with HIV is expected to grow and experience age-related cognitive declines, concerns mount that such existing cognitive impairments may become exacerbated in already cognitively vulnerable subgroups such as women with HIV. These cognitive impairments can develop into everyday functional impairment in either basic or instrumental activities of daily living. Methods In the Women’s Interagency HIV Study, we examined the association between objective cognitive test performance and the self-rated Lawton and Brody scale of Independent Activities of Daily Living (IADL) in 754 older (50+) women with HIV (WWH; 84% virally suppressed). To handle this longitudinal data, weighted logistic mixed effect models examined associations between cognitive domain performance (predictor) and functional outcomes (IADL item level scores). Results In the total sample, poorer motor performance was associated with impairments in home repairs, housekeeping, and laundry and poorer executive functioning was associated with impairment in planning social activities. Among older virally suppressed-WWH, poorer motor performance was associated with deficits in home repair and poorer executive performance was associated with deficits in planning social activities. Conclusion Since motor and executive performance were related to impairments in certain IADLs, strategies such as cognitive training targeting these domains could improve everyday functioning. Such approaches could improve autonomy as WWH age.